Inferential Discourse Markers across English and Behdini Kurdish Legal and Scientific Speeches in Simultaneous Interpreting IDMs in English-Kurdish SI - Alaa Refhat Obaid; Shivan Shlaymoon Toma (Zanco Journal of Human Sciences, 2026)
Discourse coherence is crucial in simultaneous interpreting (SI), ensuring that the target audience understands the logical flow and purpose of the speaker’s message, not just the propositional meaning. Among the elements that maintain coherence, inferential discourse markers (IDMs) such as therefore, so, thus, and as a result are particularly essential as they express reasoning, cause-effect, and conclusions. However, there is limited research on these markers in English-Kurdish interpreting. This study fills this gap by exploring how IDMs are handled in English-Kurdish SI through the analysis of two speeches (legal and scientific), with 10 interpretations produced by five Kurdish professional simultaneous interpreters. For examining the data, qualitative coding was used to identify IDMs, and a comparative analysis was used to investigate the strategies applied by the interpreters for rendering IDMs. The findings reveal that the dominant strategy was direct equivalence (DE), particularly for frequent and recognized markers, while paraphrasing (PP) and substitution (SUB) were applied for markers without fixed direct equivalents. Omission was rare, with only two instances. The results highlight the importance of training interpreters to recognize the pragmatic functions of DMs and depend on appropriate strategies for rendering them, providing implications for interpreter training and discourse studies.